STRATEGI PEMBERIAN KOMPENSASI DALAM MENINGKATKAN MOTIVASI KERJA GURU - izza nur; Resdianto Permata Raharjo (STAINU Tasikmalaya, 2023)
Provision of welfare for teachers is something that needs attention and is needed by someone to ensure their survival. The fact is that nowadays school institutions and several institutions are competing to create work welfare by fulfilling salaries or wages for all services that have been provided by members. The fulfillment of this welfare is manifested in the provision of compensation. To facilitate researchers in identifying problems related to compensation, researchers conducted research conducted at an elementary school level educational institution. This study raises the title “Compensation Giving Strategy in Increasing Teacher Work Motivation” as a problem solver and anticipation of problems being faced in increasing teacher work motivation. This scientific work was formed based on qualitative research methods that have been carried out as a form of the author’s endeavor in collecting some data that will be used as information material. In this study, several strategies were found by school principals in providing compensation and obstacles and solutions in the process of providing compensation. Preparation of a good strategy in the process of providing compensation is needed. This can have an impact on the size of the compensation given and the timing of compensation. Obstacles found can be overcome and prevented by implementing the solutions that have been described. Obstacles that arise in each institution will vary according to the ability of the institution and environmental conditions.